Development and Evaluation of a Vacuum Frying System for Banana Chips (Musa spp.) - RANASALA N; Dr. Sudheer K.P (Guide) (Tavanur 2017 DEPARTMENT OF FOOD AND AGRICULTURAL PROCESS ENGINEERING)
Development and Evaluation of a Vacuum Frying System for Banana Chips (Musa spp.) doctor of philosophy
Development and Evaluation of a Vacuum Frying System for Banana Chips (Musa spp.) doctor of philosophy